2003
DOI: 10.18388/abp.2003_3702
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of transforming growth factor beta1 in drug resistance of tumor cells.

Abstract: Acquired drug resistance of tumor cells is frequently observed in cancer patients undergoing chemotherapy. We studied murine leukemia L1210 cells sensitive and resistant to the cytotoxic action of cisplatin and showed that cisplatin-resistant leukemia cells were also refractory to TGF beta1-dependent growth inhibition and apoptosis. Addressing the question about the mechanisms responsible for the cross-resistance to cisplatin and TGF beta1, we found that cisplatin- and TGF beta1-resistant L1210 cells possessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…SMAD3:rs11632964 was the initial split on the survival tree for the chemotherapy group. It is known that (36,37). Therefore, the effect of SMAD3:rs11632964 in our study is in agreement with SMAD3-SMAD4 controlled upregulation of Bim playing an important role in TGF-b -induced apoptosis (38).…”
Section: Discussionsupporting
confidence: 89%
“…SMAD3:rs11632964 was the initial split on the survival tree for the chemotherapy group. It is known that (36,37). Therefore, the effect of SMAD3:rs11632964 in our study is in agreement with SMAD3-SMAD4 controlled upregulation of Bim playing an important role in TGF-b -induced apoptosis (38).…”
Section: Discussionsupporting
confidence: 89%
“…Studies of TGFbeta-1 and Dx co-resistance in these cell clones are ongoing in our laboratory. Data are available that cells, resistant to DNA-damaging drug cisplatin exhibit a co-resistance to TGFbeta-1 action (Stoika et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…TGFbeta-1 was shown to mediate irradiationinduced p53-dependent apoptosis in situ (Ewan et al, 2002). Moreover, data are available that the leukemia cells, resistant to cisplatin, DNA-damaging anti-tumor drug, develop crossresistance to TGFbeta-1 (Stoika et al, 2003). Doxorubicin (adriamycin) is an anthracycline drug widely used in anticancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…At the late stages of tumor progression when the tumor cells become resistant to the growth inhibition by TGF-b due to inactivation of the TGF-b signaling pathway or aberrant regulation of the cell cycle, TGF-b exhibits a pro-metastatic role [26]. Earlier it has been found that the cisplatin-resistant sub-line of murine leukemia L1210 cells possesses a cross-resistance to TGF-b 1 and the mechanism of drug resistance, based on the involvement of TGF-b 1 , has been proposed [27]. We also studied whether the above mentioned anticancer drugs can alter the expression of mRNAs for TGF-b and its receptors in the MCF-7(wt) and the MCF-7(DOX/R) cells.…”
Section: Discussionmentioning
confidence: 99%